Pairing Prosecco wine and Asiago cheese: Insights from a panel assessment and consumer test - Lomolino, Giovanna; De Iseppi, Alberto; Stiletto, Alice; Marangon, Matteo; Curioni, Andrea; Pasini, Gabriella; Vincenzi, Simone; Franceschi, Deborah; Crapisi, Antonella; Trestini, Samuele (Italian Journal of Food Science, 2025)
This study investigates the traditional pairing between Prosecco wine and Asiago cheese to identify the key sensory attributes influencing consumer preference. Three styles of Prosecco and three Asiago maturations were first evaluated separately using Descriptive Analysis. The resulting nine pairings were then tested by a trained panel and by consumers. Multivariate analyses (PCA and HCPC) were used to relate sensory profiles to consumers’ liking. Results show that consumers prefer pairings based on sensory synergy or contrast, particularly those involving sparkling Prosecco with fresh or ripened Asiago, demonstrating the key role of specific sensory attributes in determining pairing success.